Role of Working and Non-working Women in Household Decision Making : (A Case of Kohalpur Municipality-10, Banke) - Basnet Pokhrel, Sabitra (Academia Research Journal, 2023)
The objective of the study is to discover the socioeconomic position of women in Kohalpur Municipality Ward No. 10 in order to determine the variations between the roles played by working and non-working women in household decision-making, as well as the factors that influence women’s decision-making ability. This study uses both primary and secondary data in accordance with its needs. During the field survey, the sampled unit’s primary data is chosen using a structured questionnaire and an interview. In this study, both quantitative and qualitative data have been gathered and employed. Secondary information is gathered from the Kohalpur Municipality ward number 10 survey 2078. Judgment/deliberate non-random sampling have been used to choose the research households. There are 950 houses and 5148 people in total among these wards. Only 50 of the total number of households were chosen by me among them. They range in age from 16 to 59, with 25 of them employed and 25 not. The study’s conclusion is that the majority of Nepalese women reside in rural areas where their options for employment are confined to agricultural work on farms, many of which are held by their father, spouse, landowners, or siblings. Women in Nepal aren’t allowed to own property, so they must work on men’s land from dawn till sunset to support themselves and their families. Therefore, males are responsible for ensuring that women have the means to survive not only in external affairs but also in their own domestic issues, which are an essential component of their life.